Effect of 20-Hydroxyecdysone, a Phytoecdysteroid, on Development, Digestive, and Detoxification Enzyme Activities of Tribolium castaneum (Coleoptera: Tenebrionidae). Issue 5 (22nd October 2019) - Ajaha, Ayoub; Bouayad, Noureddin; Aarab, Ahmed; Rharrabe, Kacem
Abstract: Plants present a delimited reservoir of biologically active compounds. Many plants synthesize several compounds of secondary metabolism, such as alkaloids, terpenoids, phenolics, steroids, etc. Such compounds are generally thought to be involved in plant–insect interactions. Phytoecdysteroids are a class of chemicals that plants synthesize; these compounds are analogues of molting hormones produced by insects. In this work, the effect of the 20-hydroxyecdysone, which is a molecule that belongs to the family of phytoecdysteroids, was tested on an insect pest, Tribolium castaneum (Herbst). Firstly, the effect of this molecule on post-embryonic development parameters was tested after ingestion at 300, 600, 900, and 1, 200 ppm. Secondly, the effect of the 20-hydroxyecdysone was also tested on the biological parameters (proteins, alpha-amylase, detoxification enzymes). The results of the post-embryonic parameters test showed an important induction of larval mortality and a significant reduction of pupation and adult emergence rates. On the other hand, the test on the biological parameters showed that the 20-hydroxyecdysone caused a significant decrease in the levels of soluble proteins in treated larvae. In addition, the alpha-amylase activity was significantly inhibited by the ingestion of the phytoecdysteroid. And there was also a disruption of detoxification enzymes. The whole of the disturbances recorded in this work prove that phytoecdysteroids are thought to have potential value on T. castaneum control.